Coronary dominance and predictors of adverse events during coronary interventional procedures: an observational study - Paudel, Navaraj; Jha, G.S.; Alurkar, V.M.; Kafle, Ramchandra; Sapkota, Subash (Journal of Advances in Internal Medicine, 2017)
Background: Coronary dominance is associated with adverse peri-procedural events during coronary interventions. There are limited data regarding events during coronary angiography in Nepal. Aims and methods: The aim of this article is to get information regarding events during invasive procedures of this region which has a large feeder population. All the cases undergone cardiac interventional procedures were included and analyzed. Results: Out of 200 cardiac interventional procedures, 160 cases underwent coronary angiography (CAG) and 20 percutaneous coronary intervention (PCI). 54% of the study populations were male. The mean age of study population was 61.2 years (range: 29-85 years). Most common indication for performing CAG was for post ACS (69%) followed by chronic stable angina (CSA) (16%). Most common finding in CAG was SVD (35%) LAD was the commonest (55% of SVD), DVD (19%), non-critical CAD (13%), TVD (14%) and left main (2%). Myocardial bridging was seen in 2% and 15% had normal coronaries. Commonest risk factor for CAD was Hypertension (45%) followed by smoking (35%) and diabetes (16%). CAG was most commonly performed from right radial (70%) followed by right femoral (24%), left radial (5%) and left femoral (1%). 78% of patients had right dominance, 16% had left dominance while 6% had co-dominance. Out of 40 non-right dominant (left or co-dominant) patient twenty three (57.5%) were female. There was no significant association of left dominance with the gender although the odds ratio was high (1.8) in female gender (P=0.12). Considering Left dominant patients only, the odds ratio of Tiger catheter versus Judkins Right (JR) is 8.33 but not statistically significant (P=0.17). Major complications encountered were ventricular tachycardia (VT) in 4 cases. The odds for VT with left dominance and right dominance was high with statistical significance [OR: 53.48, C.I :( 2.79-1023.4); P=0.002]. Conclusion: Ventricular tachycardia which is among the major complication is found to be significantly associated with left dominance. Further studies are necessary to evaluate the evidence provided by this study.